Pengembangan Kawasan Transmigrasi Latiung sebagai Kampung Industri Pandu Trans Patriot - Mufti Petala Patria; Gadis Sofyan Humaira; Puti Intan Az-Zahra Esmano; Shafa Fajriya Anindita Qurnain (Yayasan Literasi Sains Indonesia, 2026)
Simeulue Regency possesses abundant natural resources; however, their utilization remains limited to the sale of raw materials with low added value and suboptimal waste management. This study aims to identify potential flagship commodities and formulate a development design for the Latiung transmigration area as a sustainable agro-industrial hub. Using a descriptive qualitative-quantitative method with a participatory approach, the research involved field observations, in-depth interviews, and Focus Group Discussions (FGD) across 23 villages in South Teupah and Central Teupah Districts. The findings indicate that coconut, cloves, oil palm, areca nut, and the livestock sector are strategic commodities requiring downstream intervention. As a primary output, this research formulates the